Unusual presentation of JAK2-negative polycythemia - Thomas, Akesh; Robert, Alex; Chemplavil, Don Babu (Indian Journal of Case Reports, 2018)
Polycythemia vera is a relatively rare disease occurring in 0.02–2.8 per million population. Globally, about 95% of PV is dueto JAK2V617F mutation in the chromosome 9p. The remaining 5% were found to have a wide range of mutations includingJAK2 exon12 mutation and calreticulin (CALR) mutation. In India, the incidence of JAK2-negative polycythemia is relativelyhigh, reaching up to 18%. Polycythemia usually presents as symptoms secondary to hyperviscosity or as symptoms secondary toincreased histamine release by the cells. Herein, we describe a 46-year-old Indian male presented with a headache and found to bein hypertensive urgency, which was later found to be secondary to JAK2-negative polycythemia.